PERAN BADAN PERMUSYAWARATAN DESA DALAM PEMBANGUNAN DESA DI DESA COMPANG NDEJING - Andelo, Claudio Adventino Pandy; Indriani, Maria Apriliana; Lete, Christian Geo Bone Reda; Lawalu, Stephanie Perdana Ayu; Pantola, Bruno Rey Sonbay (Jurnal Pengabdian Multidisiplin Indonesia (JUPEMI), 2025)
This article discusses a community service program in the form of socialization of the importance of the role of the Village Consultative Body in village development for members of the Village Consultative Body in Purang Mese, Compang Ndejing Village, Borong District, East Manggarai Regency. This activity is motivated by the importance of the Village Consultative Body realizing its main tasks and functions in village development. The purpose of this program is to increase awareness of the Village Consultative Body regarding its main tasks and functions. The methods used include observation, simulation, evaluation, and feedback. This activity was carried out on April 15, 2025, involving the Village Consultative Body (BPD) and all village officials. The material provided includes Understanding the Village Consultative Body. Duties and Functions of the Village Consultative Body, the Role of the Village Consultative Body in Village Development, the Role of the Village Consultative Body in Decision Making, the Role of the Village Consultative Body in Supervising Village Funds, Challenges Faced by the Village Consultative Body in Village Development.